БОШЛАНҒИЧ СИНФ ЎҚУВЧИЛАРИГА ЖИСМОНИЙ ТАРБИЯ ВА СПОРТ ТАДБИРЛАРИ ОРҚАЛИ МИЛЛИЙ ҚАДРИЯТЛАРНИ СИНГДИРИШ УСУЛЛАРИ - Ахмедов, Ф.Қ.; Атамуродов, Ш.Ў. (SCIENCE and SOCIETY, 2020)
The article is devoted to the study of issue of human emotions, which are national values through physical education and sports activities for students of grades 1-4.